Impact of Transcranial Direct Current Stimulation on Dual-Task Gait Performance in Parkinson's Disease: A Systematic Review. - Moeyersons, Charlotte; Karagiannidou, Evgenia; Al Omari, Sarah; Swinnen, Eva; Firouzi, Mahyar (NeuroRehabilitation, 2025)
Background: Parkinson's disease (PD) impairs motor and cognitive functions, increasing fall risk during dual-task activities. While transcranial direct current stimulation (tDCS), a non-invasive brain stimulation technique, has been studied for improving these functions in PD, its effect on dual-task gait remains unclear. Objective: This review aims to evaluate the effects of tDCS on dual-task gait performance in PD. Methods: A systematic search was conducted in PubMed, Embase, and Web of Science for studies published before September 2024. Eligible studies included PD patients, used tDCS, and measured dual-task gait performance. Two researchers independently assessed methodological quality using the Cochrane Risk of Bias tool. Results: Four randomized controlled trials and four crossover studies, involving 222 PD patients (mean age 64.17 years, range 50.9–72) at Hoehn & Yahr stages 1–3, met the inclusion criteria. Three of six studies targeting the dorsolateral prefrontal cortex showed significant improvements in dual-task gait performance, particularly in gait speed (p ≤ 0.046), compared to sham. No significant improvements were observed with primary motor cortex or cerebellar stimulation (all p 's ≥ 0.100). Conclusions: tDCS targeting the dorsolateral prefrontal cortex may improve dual-task gait performance in PD, but further studies are needed to refine protocols and confirm its therapeutic potential.